225k views
0 votes
Factor the expression completely.

2x^2-16x+32

User Dan Belden
by
5.8k points

1 Answer

4 votes

Answer:

2(x - 4)(x - 4)


Explanation:

2x²-16x+32

First find the sum and the product of this expression

sum = -16

product = 2×32 = 64.

Which are this 2 numbers (factors) such that when you multiply them you get 64 and when you add them you the result is -16.

These factors are:

-8 and -8

2x² - 16x + 32 = 2x² -8x - 8x + 32

= 2x(x - 4) - 8(x - 4)

= (x - 4)(2x - 8)

= 2(x - 4)(x - 4)


User Amr Elgarhy
by
5.1k points